Urban Landscape Improvement for Creative Cultural Tourism in Tha-Chanuan Subdistrict and Siladan Subdistrict, Manorom District, Chainat Province - Choatpanyatum, Yiampol; Kitnukoon, Jomyot; Konprom, Sajja (Rajamangala University of Technology Tawan-ok Research Journal, 2024)
Manorom is a town with a long and interesting history. Significant archaeological sites and artifacts have been excavated in many areas, which remain rich in natural ecosystems. The lowland soil in many parts is suitable for agriculture in several sub-districts. Additionally, various areas in Manorom District have the potential to be developed and landscaped into attractive agro-tourism, eco-tourism, and cultural tourism destinations that are beautiful, interesting, and can mitigate natural disasters. However, the current condition still lacks proper management. Some areas remain abandoned and neglected, including riverside areas along the Chao Phraya River and ponds or lakes. Therefore, the design and improvement of urban and sub-area landscapes in several areas can promote development into open spaces for community recreation in each sub-district, as well as areas that can accommodate various tourist activities. This will promote the arts, culture, traditions, and way of life of the community, making them interesting and worthy of visiting. As a result, it will become a well-known tourist destination that can be improved to accommodate tourists in the future. This research is part of the complete research report titled “Manorom” urban landscape improvement for creative cultural tourism. The concept was to survey, collect data, design urban community landscape improvements, sub-area landscape improvements, and create creative cultural tourism routes phase 2 in Tha Chanuan and Siladan sub-districts. This aims to lead to the management of creative cultural tourism in Manorom District, Chainat Province, with efficiency and effectiveness. The objectives were 1) to design and develop the town as a creative cultural tourism destination, and 2) to propose landscape improvement designs for Tha Chanuan and Siladan sub-districts in Manorom to transform the town into a creative cultural tourism city. The development goals were divided into two parts: 1) improvement of three types of tourism routes, and 2) Phase 2 of landscape improvements in certain areas of Tha Chanuan and Siladan sub-districts. The urban community landscape improvement design in areas representing the identity of each sub-district involved compiling information and proposing tourism routes that align with the town’s identity. The tourism routes were designed to divide into three main types: creative historical and cultural tourism routes, creative agricultural lifestyle tourism routes, and creative traditional tourism routes. These routes were designed to serve as guidelines and travel plans for tourists and visitors to explore Manorom, particularly in Tha Chanuan and Siladan sub-districts. The proposed landscape improvements can be used to benefit tourism and enhance the quality of life for the community. Residents of the sub-districts can use the spaces for recreation, relaxation, and other leisure activities, both passive and active. The design of the areas follows the concept of creative city design, avoiding environmental destruction, enhancing biodiversity, and being environmentally friendly. It also ensures no negative impact on the traditional way of life of the local population.